The Effects of Self-Directed Learning Strategy on Studints’ Reading Comprehension Skills - Cicuk Rammayadi S.; Juhana Juhana; Ruminda Ruminda (Scope : Journal of English Language Teaching, 2023)
This research aims to describe the implementation of self-directed learning (SDL) for the tenth-grade students of SMK PGRI 2 Tanah Grogot, to analyze the effectiveness of the self-directed learning (SDL) strategy on reading comprehension skills for the tenth-grade students of SMK PGRI 2 Tanah Grogot and to analyze the student's motivation after the application of the self-directed learning (SDL) strategy of reading comprehension skills for the tenth-grade students of SMK PGRI 2 Tanah Grogot. This research used experimental investigation methods. The target population and sample of this research were all tenth-grade students of SMK PGRI 2 Tanah Grogot for the academic year 2022/2023. The total sample was 14 students. The findings of the research show that the efficiency of using self-directed learning strategy can be known from pre- and post-test comparison findings. It can be seen from the acquisition of the means of the pre-test was 43.1429 and the post-test was 85.4286 which was carried out on the same 14 samples. The questionnaire's findings answers showed that student motivation increases after carrying out the learning process. It can be seen from the frequency distribution of questionnaire statements using the Likert Scale. Based on the findings, it is possible to deduce that the use of self-directed learning strategies improves students' reading comprehension skills and motivation.